Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian pada Konsumen Pakaian di Toko Serba 35.000 Bima - Melinda Eka Kartika; Muhajirin; Feni Aryani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the effect of product quality and price on consumers’ purchasing decisions for clothing at Toko Serba 35.000 Bima. A quantitative approach with an associative research method was applied to examine the relationship between the independent variables, namely product quality (X1) and price (X2), and the dependent variable, purchasing decision (Y). Data were collected using questionnaires distributed to 96 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that product quality has no significant effect on purchasing decisions, whereas price has a positive and significant effect. Furthermore, the simultaneous test reveals that product quality and price together significantly influence purchasing decisions. These findings suggest that consumers at Toko Serba 35.000 Bima prioritize price considerations over product quality when making purchasing decisions. This study provides practical insights for business owners in formulating pricing strategies and enhancing competitiveness in the local retail market.